IDENTIFICATION OF BACTERIAL CONTAMINANTS ON GLASSES USED BY STUDENTS OF FACULTY OF MEDICINE, UNIVERSITAS AIRLANGGA, SURABAYA, INDONESIA CLASS OF 2016 - Hana Letitia Anjani; Marijam Purwanta; Maftuchah Rochmanti (Majalah Biomorfologi, 2021)
Background: People nowadays suffer from refractive disorder that declines the vision. The most common therapy to overcome this problem is to use glasses. The continuous use of glasses and the difficulties on disinfecting the entire surface can cause bacterial contamination. Those bacteria can cause various eye diseases. This fact pushed the researcher to find out if there were bacterial contaminants on glasses used by students of Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, class of 2016. Objective: To prove the species of bacterial contaminants and pathogenic bacteria on glasses used by students of Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia class of 2016. Materials and Methods: Cotton swab moistened in sterile distilled water was swabbed to 30 glasses on its inside lens and the part touching the nose. The sample was then inoculated on blood agar and Mac Conkey, and incubated for 24 hours in 37oC. Then, the isolates were identified macroscopically and microscopically. Results: The whole sample that had been examined was contaminated with pathogenic bacteria with risk of causing eye diseases. Those bacteria were identified as Bacillus sp. (50%), Pseudomonas sp. (46%), Staphylococcus aureus (20%), and Staphylococcus epidermidis (16%). Conclusion: The result of this research showed that there was contamination by bacteria on glasses used by students of Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia class of 2016. All bacteria found were pathogenic to the eye. This showed that glasses could become a reservoir of the pathogenic bacteria that could potentially cause recurring eye infection.